2016
DOI: 10.1155/2016/9729818
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Melissa officinalis Leaf Extract on Long‐Term Memory in Scopolamine Animal Model with Assessment of Mechanism of Action

Abstract: Melissa officinalis (MO, English: lemon balm, Lamiaceae), one of the oldest and still most popular aromatic medicinal plants, is used in phytomedicine for the prevention and treatment of nervous disturbances. The aim of our study was to assess the effect of subchronic (28-fold) administration of a 50% ethanol extract of MO leaves (200 mg/kg, p.o.) compared with rosmarinic acid (RA, 10 mg/kg, p.o.) and huperzine A (HU, 0.5 mg/kg, p.o.) on behavioral and cognitive responses in scopolamine-induced rats. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 71 publications
1
43
1
Order By: Relevance
“…Our previous studies have reported significant amounts of salvianolic acid B in transformed root cultures and the roots of a 1-year-old intact plant of D. forrestii (Weremczuk-Jeżyna et al 2016). In contrast to caffeic and rosmarinic acid, salvianolic acids are not common and have been found in only a few species (Ożarowski et al 2016;Ribeiro et al 2016;Cirlini et al 2016). They are mainly obtained from members of the Salvia genus, especially Salvia milthiorrhiza (Li et al 2009a).…”
Section: Identification Of Phenolic Compounds Of the Hydromethanolic mentioning
confidence: 99%
“…Our previous studies have reported significant amounts of salvianolic acid B in transformed root cultures and the roots of a 1-year-old intact plant of D. forrestii (Weremczuk-Jeżyna et al 2016). In contrast to caffeic and rosmarinic acid, salvianolic acids are not common and have been found in only a few species (Ożarowski et al 2016;Ribeiro et al 2016;Cirlini et al 2016). They are mainly obtained from members of the Salvia genus, especially Salvia milthiorrhiza (Li et al 2009a).…”
Section: Identification Of Phenolic Compounds Of the Hydromethanolic mentioning
confidence: 99%
“…and thyme (Thymus spp.) species, lemon balm (Melissa officinalis L.), common sage (Salvia officinalis L.), oregano (Origanum vulgare L.), and sweet basil (Ocimum basilicum L.) [35][36][37]. Another well-known secondary metabolite, the phytohormone salicylic acid (SA), is a key signaling compound that participates in the plant response to pathogens, herbivores, and abiotic stress [38].…”
Section: Citric Acidmentioning
confidence: 99%
“…2,3 Lamiaceae species have been used in traditional medicine for the treatment of depression, headache, asthma, 4 stress, 5 and respiratory 6 and Alzheimer's diseases. 7,8 In addition, these plants have antioxidant, 9 antiallergic, 10 antimicrobial, 11 anticarcinogenic, 12 anti-inflammatory, 13 astringent, 14 and antiHIV-1 effects. 15 These properties are mainly due to phenolic compounds found in the plants, especially rosmarinic acid (RA).…”
mentioning
confidence: 99%